Research Topic: Impact of Money Laundering on Economic Growth Case study: Nile Commercial Bank – Juba South Sudan - Ayoker , Lam Bukeje (IJRDO - Journal of Business Management, 2022)
The aims of this study is to analyze the impact of money laundering on economic growth and to know measures taken by government to prevent the money laundering activities in South Sudan. The researcher used qualitative and quantitative methods for collecting data; also the researcher used the statistical package for social science (SPSS) for data analysis. Findings: The study revealed that money laundering has impact on economic growth of the country, money laundering could cause inflation, there is Act of Anti –money laundering in South Sudan, money laundering promoting corruption, senior management is responsible to manage money laundering Recommendation: researcher has reached to the important recommendations as following;